Screening and referral is not enough: a qualitative exploration of barriers to access and uptake of mental health services in patients with cardiovascular diseases - C. M. Collopy; S. M. Cosh; P. J. Tully (BMC, 2021)
Abstract Background Cardiovascular diseases (CVD) are commonly comorbid with mental health disorders, portending poorer cardiac prognosis. Despite the high prevalence of depression and anxiety, and guidelines recommending routine depression screening and referral, uptake of mental healthcare in CVD populations remains low. Reasons for the underutilisation of mental health and psychological services for this population remain largely unknown. Methods Thirteen CVD patients with clinically significant psychological symptoms (depression, anxiety and/or stress) participated in one-on-one in-depth semi-structured interviews. Data were analysed using inductive thematic analysis. Results Barriers to uptake included the timing of referral and screening, with patients reporting a need for longer term follow-up. A lack of information provision and understanding around mental health and services, especially following cardiac-events were further barriers. A reluctance to report mental health or engage in services was also identified, with patients indicating a preference for informal peer support networks. A range of practical barriers such as mobility, transport and cost were also reported. Conclusions Longer term follow-up and routine mental health assessment may be beneficial to facilitate use of mental health services. Upskilling of practitioners around mental health may be a further avenue to promote information provision and enhance service use. Further focus on enhancing informal peer support may be a valuable initial approach for the CVD population. The implications for improving services and enhancing service use are discussed.